On Locally Linearly Convex Domains - Zelinskii, Yu. B. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We construct a counterexample to the hypothesis on global linear convexity of locally linearly convex domains with everywhere smooth boundary. We refine the theorem on the topological classification of linearly convex domains with smooth boundary.